Now is good, earlier is better. - Tobert, J; Preiss, D (Oxford University Press, 2017)
There is abundant evidence that lowering LDL cholesterol with statins reduces cardiovascular risk both in those without symptomatic atherosclerotic disease (primary prevention), and those who have already suffered an atherosclerotic complication, such as a myocardial infarction or ischaemic stroke (secondary prevention).